Will you be a honey and help us raise money?: investigating online crowdfunding platforms acceptance, perceived trust and behavioural intention / Saiyid Abdallah Syahir Al-Edrus, Ismail Ahmad and Mohd Hafiz Hanafiah - Syahir Al-Edrus, Saiyid Abdallah; Ahmad, Ismail; Hanafiah, Mohd Hafiz (UiTM Press, 2023)
Despite the emerging acceptance of online crowdfunding platforms being apparent among small entrepreneurs, its adoption among general users is significantly low. Hence, this study investigated the factors influencing user acceptance, perceived trust and usage intention with online crowdfunding platforms. Empirical data were collected from 300 crowdfunders. The Partial-least Square-Structural Equation Modeling (PLS-SEM) was utilised to confirm the study model and hypotheses. The results indicated that the crowdfunding platforms' performance expectancy, social influence, user habit, and perceived trust significantly predict users' behavioural intentions. In contrast, the study confirmed that online crowdfunding platforms' effort expectancy, facilitating condition, hedonic motivation, and price value were not significant determinants of crowdfunding platforms' user behavioural intention. The findings provide new insights into the role of perceived trust in the UTAUT model and user adoption of online crowdfunding platform contexts, which offer significant theoretical and managerial implications for small business crowdfunders.